Resiliencia y funcionalidad familiar en estudiantes de nivel secundaria de la Institución Educativa N° 60276 Eugenio Rivera López Islandia 2024 - Rodriguez Correa, Pedro Pablo (2025)
The aim of this study was to determine the relationship between resilience and family functionality among secondary-level students of Educational Institution No. 60276 “Eugenio Rivera López” in Islandia during 2024. A basic, quantitative, non experimental, correlational, and cross-sectional design was used; the population comprised 283 enrolled secondary students, and a census sampling approach was applied. Data were collected through two validated questionnaires: one on resilience (based on Wagnild and Young’s five factors) and one on family functionality (based on the Apgar model). Results showed a strong and statistically significant positive correlation between the two variables (Spearman’s Rho = 0.819; p < 0.001). Specifically, the dimensions of resilience displayed very high correlations: self confidence (Rho = 0.862), equanimity (Rho = 0.750), perseverance (Rho = 0.824), personal satisfaction (Rho = 0.790), and comfort with being alone (Rho = 0.933); all with p < 0.001. It is concluded that the family constitutes a key protective environment for the development of resilient skills in adolescents; therefore, strengthening family dynamics directly impacts their emotional well-being and academic performance.